(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, in order to study the nature of the comic phenomenon, one can see the different views and opinions of a number of philosophers. Each philosopher explained the philosophical interpretation of comedy with different examples.